2009
DOI: 10.1590/s1808-86942009000400015
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing and quality of life after total laryngectomy and pharyngolaryngectomy

Abstract: Dysphagi a can be a consequence of total laryngectomy even in the absence of symptoms and it could indeed directly or indirectly compromise quality of life. Aim: To evaluate the characteristics of swallowing after total laryngectomy and pharyngolaryngectomy with pharyngeal T closure, correlating them with the Quality of Life in Swallowing Disorders questionnaire. Methods: A prospective evaluation was performed in 28 patients; fifteen undergoing total laryngectomy and thirteen undergoing total pharyngolaryngect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 20 publications
1
45
2
Order By: Relevance
“…When we compared the values obtained by the healthy elderly to other populations, in completely dysphagic individuals (in different levels and different foundation pathologies), we observed great differences, being that the proven dysphagia, generally, result in very inferior mean scores (20,27) .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…When we compared the values obtained by the healthy elderly to other populations, in completely dysphagic individuals (in different levels and different foundation pathologies), we observed great differences, being that the proven dysphagia, generally, result in very inferior mean scores (20,27) .…”
Section: Discussionmentioning
confidence: 94%
“…Another study, about quality of life related to swallowing in cancer patients (27) , found scores between 63 and 88 points in the 11 domains. The worst medians were obtained in the domains burden (63 pints), communication (63 points), mental health (65 points), social function (65 points) and frequency of symptoms (63 points).…”
Section: Discussionmentioning
confidence: 99%
“…16 It includes complete disease clearance and organ preservation determined by tumor extension, the amount of tissue remaining and the later plan for reconstruction. 17 Surgery for piriform fossa malignancies include removal of the total larynx and the part of the pharyngeal wall on which the tumor invaded onto and clearance of the draining interjugular lymph node levels. 17 Aspiration causing swallowing problems are not seen after total laryngectomy as airway and pharyngoesophagus are physically separated.…”
Section: 15mentioning
confidence: 99%
“…17 Surgery for piriform fossa malignancies include removal of the total larynx and the part of the pharyngeal wall on which the tumor invaded onto and clearance of the draining interjugular lymph node levels. 17 Aspiration causing swallowing problems are not seen after total laryngectomy as airway and pharyngoesophagus are physically separated. 18 The greatest difficulty with deglutition is in propulsion of the bolus through the oral cavity and pharyngoesophageal segment where the cleft in the palate in our case formed a technical contraindication for the surgical procedure.…”
Section: 15mentioning
confidence: 99%
See 1 more Smart Citation